Estimativa dos parâmetros da equação de Van Genuchten com dados de umidade do solo e modelagem inversa com Hydrus-1D - Costa, Tancio Gutier Ailan (2019)
The relationship between the water content and the energy with which it is retained in the soil can be expressed graphically constituting the soil water characteristic curve (SWCC). Traditionally it is obtained in the laboratory, with the adjustment of the data by several models, being van Genuchten (1980) one of the most used. Although routinely, obtaining the SWCC in the laboratory requires a lot of time and, therefore, we have been looking for ways to optimize the time possible with less labor expenditure, as long as good data quality is maintained. For this purpose, the modeling, and consequently the Hydrus-1D model, is inserted as the possibility of obtaining the said curve. In this case, the hypothesis was considered that with the reverse modeling using Hydrus-1D it is possible to simulate the coherent soil water redistribution to the process verified in the field and to estimate with better accuracy the SWCC with soil moisture data obtained in the field than those obtained in the laboratory. The objective of this study was to estimate the parameters of the van Genuchten equation in five soil texture classes with soil samples in the laboratory and by inverse modeling with moisture data (obtained by gravimetry) in field experiments. In all cases, the estimation of the parameters occurred with five replications. The parameters of the van Genuchten equation were submitted to analysis of variance (F test at 5% significance), with Tukey's test, also at 5% significance. The efficiency in the prediction and accuracy of the simulated results was measured by the Nash and Sutcliffe - COE efficiency coefficient, and by the root mean squared root - RMSE. Reverse modeling simulated satisfactorily the redistribution of water in the soil for all textural classes, given the low error values of the data and the good agreement between those observed in the field and the simulated ones. In addition, the soil water characteristic curves obtained in the laboratory overestimated those obtained by the inverse model, making the results obtained by Hydrus - 1D more faithful to the representation of water dynamics under field conditions. It was concluded that the use of Hydrus-1D allows to estimate the parameters of the van Genuchten equation in a way more coherent with the data obtained in situ than those obtained in the laboratory for all textural classes, estimating with better accuracy the water content in the soil independently of the textural class of soil.